2019
DOI: 10.1016/j.foodchem.2018.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomic profiling of human milk with LC–MS/MS reveals pH-specific proteolysis of milk proteins

Abstract: Human milk is a dynamic protein-protease system that delivers bioactive peptides to infants. The pH of milk changes from the mother’s mammary gland to the infant’s digestive tract. Although the release of human milk peptides has been studied during in vivo or in vitro digestion, these models did not explicitly vary nor observe the effect of pH. The objective of this research was to determine the effect of pH on the proteolysis of human milk. Using high-resolution accurate-mass Orbitrap mass spectrometry, profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 36 publications
(45 reference statements)
2
19
0
Order By: Relevance
“…Different authors demonstrated the prevalence of β-casein derived peptides in HM (72; 73; 74). Scarce presence of peptides derived from major whey protein, in particular from αlactalbumin, characterized the studied samples, as reported for HM by Gan et al (75).…”
Section: Discussionsupporting
confidence: 61%
“…Different authors demonstrated the prevalence of β-casein derived peptides in HM (72; 73; 74). Scarce presence of peptides derived from major whey protein, in particular from αlactalbumin, characterized the studied samples, as reported for HM by Gan et al (75).…”
Section: Discussionsupporting
confidence: 61%
“…Thus, human milk can be viewed as a dynamic signal delivery system containing esterified and free bioactive lipids. Recent studies revealed that bioactive peptides that are encrypted in human milk proteins can be released by proteolytic enzymes upon pH activation during infant digestion (Gan et al, 2019b; Gan et al, 2019c). A similar, enzyme‐based release mechanism for the controlled delivery of bioactive human milk lipids may exist within the gut of infants.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolysis of human milk was performed as described previously with slight modifications . For the first 500 µL aliquot of human milk, 500 µL of 2× protease inhibitor cocktail (Roche, 05892970001) was added and kept on ice to prevent proteolysis as the no‐incubation control.…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation at 15 000 × g at 4 °C for 10 min, peptides from the supernatant were purified by solid‐phase extraction with C18 96‐well plate (GlySci, FNSC18). Peptidomic profiling was performed by LC‐MS/MS with Q Exactive Plus Orbitrap Mass Analyzer (Thermo Scientific) as previously described . Briefly, samples were resuspended with 0.1% formic acid in 2% acetonitrile.…”
Section: Methodsmentioning
confidence: 99%